Prevalence of Latent Tuberculous Infection in Patients With Nontuberculous Mycobacterial Lung Disease and Colonization: A Prospective Study in an Intermediate Tuberculosis Burden Country. (9th February 2022) - Lee, Ho-Sheng; Wei, Yu-Feng; Tsai, Yi-Jung; Wang, Ping-Huai; Chen, Chung-Yu; Pan, Sheng-Wei; Shu, Chin-Chung
Abstract: Background: Controlling latent tuberculosis infection (LTBI) is important in eliminating tuberculosis (TB); however, the prevalence of LTBI has rarely been studied in patients with nontuberculous mycobacterial (NTM) lung disease (LD) and colonization (LC). Methods: We prospectively recruited subjects with NTM isolated from sputum mycobacterial cultures from December 2011 to June 2019. NTM-LD and NTM-LC were defined according to the American Thoracic Society guidelines. Patients with negative cultures were recruited as controls. Patients with a history of active TB or positive TB cultures were excluded. LTBI was confirmed using a QuantiFERON-TB Gold In-tube test. The prevalence and factors associated with LTBI were analyzed. Results: A total of 406 participants were enrolled, including 171 in the NTM-LD group, 153 in the NTM-LC group, and 82 in the control group. The prevalence of LTBI was higher in the NTM-LD and NTM-LC groups than in the controls (21.6%, 20.9%, and 6.1%; P  = .006). Multivariable analysis showed that old age (adjusted odds ratio [aOR], 1.021, per year increment; P  = .042), NTM-LD (aOR, 4.030; P  = .005), NTM-LC (aOR, 3.610; P  = .011, compared with the controls), and pulmonary cavitary lesions (aOR, 3.393; P  = .034) were independently associated with LTBI. Conclusions: The prevalence of LTBI was higher in the patients with NTM-LD and NTM-LC than in the controls. Old age, pulmonary cavitation, and NTM isolated from sputum were associated with a higher risk of LTBI.